PREVALENCE AND RISK FACTORS OF HBV, HCV, AND HIV INFECTIONS AMONG TRANSGENDER INDIVIDUALS IN MARDAN AND CHARSADDA DISTRICTS, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Transgender individuals face disproportionate health risks, particularly from sexually transmitted viral infections, due to unsafe sexual practices, injection drug use, and widespread social discrimination that limit their access to healthcare services. Despite being a highly vulnerable group, there is limited epidemiological data on the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) among transgender populations in Pakistan. This cross-sectional study was conducted among 250 transgender participants aged 18–40 years (median age 19) residing in the Mardan and Charsadda districts of Khyber Pakhtunkhwa. Venous blood samples were collected in gel tubes and screened for HBsAg, anti-HCV, and anti-HIV using immune chromatographic tests (ICT), with positive cases confirmed through real-time polymerase chain reaction (PCR). Data were analyzed using SPSS version 26 to identify prevalence rates and associated risk factors. The results revealed that 1.6% of participants were positive for HBV, 5.2% for HCV, and 4.4% for HIV, with HIV showing the highest prevalence. The major risk factors associated with these infections were unsafe sexual activity, previous blood transfusions, injection drug use, and low educational attainment. These findings demonstrate a concerning level of HIV and HCV prevalence in this community, highlighting the urgent need for awareness programs, preventive strategies, and equitable access to healthcare services. Addressing the health challenges faced by transgender populations is essential not only for their well-being but also for reducing the wider public health burden of viral infections in Pakistan.